Transformational and Democratic Leadership Effects on Teachers’ Performance in Secondary Education - Emawati (BRIDGE : The Multidisciplinary Research Portal, 2025)
Leadership effectiveness remains a critical determinant of teacher performance and organizational quality in secondary education. Grounded in leadership and educational management theory, this study investigates the extent to which transformational and democratic leadership styles contribute to teacher performance. A quantitative correlational design was employed, involving data collected from 56 junior high school teachers through validated questionnaires and documentation. Multiple linear regression analysis was applied to examine both the individual and combined effects of the two leadership styles. The findings reveal that transformational and democratic leadership exert significant and positive influences on teacher performance (p < 0.05), with transformational leadership demonstrating a comparatively stronger effect. Transformational leadership enhances performance by fostering vision, motivation, and intellectual stimulation, whereas democratic leadership strengthens performance through participatory decision-making, shared responsibility, and collaborative school governance. The results support the theoretical proposition that effective educational leadership is multidimensional and integrative rather than singularly directive. This study contributes to the educational leadership literature by providing empirical evidence on the complementary roles of transformational and democratic leadership in shaping teacher performance and organizational climate. Despite its contributions, the study is limited by a restricted sample scope and the exclusion of mediating variables such as job satisfaction, professional development, and organizational support. Future research is encouraged to adopt broader samples, longitudinal designs, and expanded models to further explain the mechanisms linking leadership styles and teacher performance. Overall, the findings emphasize the strategic importance of balanced leadership practices in improving educational effectiveness and sustaining school performance.